Peranan Gerakan Literasi Terhadap Pemahaman Berbahasa - Azizi Rizal Maula (Universitas Katolik Widya Karya Malang, 2023)
This journal explains how to improve language comprehension through literacy education in SD or what is often called the School Literacy Movement (GLS). The School Literacy Program is designed using the Read-Summary-Tell-Share method. The subjects of this study were all students including low grades (1, 2 and 3) and high grades (grades 4, 5 and 6), educators (teachers), education staff, principals and librarians. This research was carried out according to the stages of student development based on their characteristics; 1) implemented in a balanced manner; 2) use a variety of texts and pay attention to the needs of students; takes place in an integrated and holistic manner in all areas of the curriculum; 3) carried out on an ongoing basis; 4) involving oral communication skills; 5) considering the diversity and condition of schools. The results of this study students understand the language properly and correctly.